The Total Capitance, Transient and Frequency Response of MFB, FDNR and Leaperog Techniques For Bilinear Switched-Capacitor Network - C. M Hadzer; M. Izhar (Universitas Gadjah Mada, 2000)
The Total Capitance, Transient and Frequency Response of MFB, FDNR and Leaperog Techniques For Bilinear Switched-Capacitor Network